Frequency of Different Histopathological Findings of Ovarian Masses Presenting at SKBZ/CMH, Muzaffarabad - Shafquat, Faiza; Zubair, Maryam (Indus Journal of Bioscience Research, 2025)
Background: Ovarian masses represent a frequent gynecological problem, encompassing both benign and malignant lesions. Their clinical and radiological presentations often overlap, making histopathological evaluation essential for definitive diagnosis, treatment planning, and prognosis assessment. Regional data are limited, particularly in Muzaffarabad, Azad Kashmir, where socioeconomic and healthcare factors may influence disease presentation. Objective: To determine the frequency of different histopathological findings of ovarian masses presenting at CMH, Muzaffarabad. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from October 2024 to March 2025 in the Department of Obstetrics and Gynecology, CMH Muzaffarabad. Methodology: A total of 183 women aged 20–70 years with ovarian lesions greater than 1 cm on ultrasound and abdominal pain persisting ≥1 month were included through consecutive sampling. Patients with malignancies in other organ systems or metastatic ovarian involvement were excluded. Clinical and demographic details were documented, and surgical specimens were analyzed histopathologically. Results: The mean age was 45.15±10.29 years, with most patients being married (85.8%) and from rural areas (59.0%). Histopathological analysis revealed benign lesions in 78.7% of cases and malignant tumors in 21.3%. Malignancy was significantly more frequent in women older than 45 years (34.1% vs. 8.7%, p